Synthesis of Ibuprofen Monoglyceride Using Novozym®435: Biocatalyst Activation and Stabilization in Multiphasic Systems - Marianela Ravelo; M. Esther Gallardo; Miguel Ladero; Felix Garcia-Ochoa (Catalysts, 2022)
This work was focused on the enzymatic esterification of glycerol and ibuprofen at high concentrations in two triphasic systems composed of toluene+ibuprofene (apolar) and glycerol or glycerol–water (polar) liquid phases, and a solid phase with the industrial immobilized lipase B from Candida antarctica named Novozym®435 (N435) acting as the biocatalyst. Based on a preliminary study, the concentration of the enzyme was set at 30 g·L−1 and the stirring speed at 720 r.p.m to reduce external mass transfer limitations. To obtain more information on the reaction system, it was conducted at a wide range of temperatures (50 to 80 °C) and initial concentrations of ibuprofen (20–100 g·L−1, that is, 97 to 483 mM). Under these experimental conditions, the external mass transfer, according to the Mears criterion (Me = 1.47–3.33·10−4 << 0.15), was fast, presenting no limitation to the system productivity, regardless of the presence of water and from 50 to 80 °C. Considering that the enzyme is immobilized in a porous ion-exchange resin, limitations due to internal mass transfer can exist, depending on the values of the effectiveness factor (η). It varied from 0.14 to 0.23 at 50 to 80 °C and 0.32–1 mm particle diameter range in the absence of water, and in the same ranges, from 0.40 to 0.66 in the presence of 7.4% w/w water in the glycerol phase. Thus, it is evident that some limitation occurs due to mass transfer inside the pores, while the presence of water in the polar phase increases the productivity 3–4 fold. During the kinetic study, several kinetic models were proposed for both triphasic reacting systems, with and without first-order biocatalyst deactivation, and their fit to all relevant experimental data led to the observation that the best kinetic model was a reversible hyperbolic model with first-order deactivation in the anhydrous reaction system and a similar model, but without deactivation, for the system with added water at zero time. This fact is in sharp contrast to the use of N435 in a water-glycerol ...